Hodgkin’s Disease: Internal Mammary Lymph Nodes Relapse Diagnosed by Gallium-67 Scintigraphy - Herná, Gloria Ruíz; Pallardó, Y.; Garcia Conde, J.; Ramos, D.; Ampudia, J.; Castillo, F. J.; Romero, C. (Nuklearmedizin - NuclearMedicine, 1999)
This article presents the case of a 62-year-old man with treated Hodgkin’s disease who had internal mammary lymph nodes relapse after a complete initial response. These masses were gallium avid. These findings were explained by histologically documented Hodgkin’s relapse, the first such case reported in that localization without chest wall involvement. The literature on mediastinal Hodgkin’s disease and diagnostic procedures are reviewed.
Keywords: Hodgkin’s disease; internal mammary relapse; Ga-67 scintigraphy